2019
DOI: 10.22490/21456453.2415
|View full text |Cite
|
Sign up to set email alerts
|

Análisis histórico de la composición química de forrajes tropicales en Colombia entre 1985 – 2015. I - Gramíneas Forrajeras

Abstract: Para evaluar dinámicas en composición nutricional de forrajes tropicales utilizados para la producción bovina en Colombia, se adelantó una revisión sistemática en un motor de búsqueda inespecífico, de investigaciones publicadas en Colombia entre 1985 y 2015 que incluyeran reportes de fracciones químicas asociadas a calidad forrajera y parámetros productivos animales. Se seleccionaron como componentes:  Proteína Cruda, Fibra Detergente Neutro, Fibra Detergente Acida y Digestibilidad In Vitro de la Materia Seca.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…The fourth group was formed by C. purpureus with the Maralfalfa and Elephant varieties with the highest yields (total biomass and DMY). Under conditions of the Ecuadorian Amazon [45] (1426 mm, 23.7 °C and 83.8%, rainfall, average temperature and relative humidity) reported values higher than 90 t.ha -1 and 20 t.ha -1 of biomass and dry material; respectively. These variations are given by natural causes or by human action such as: the availability of water, development of the root system of the plant and time of year; these produce morphological changes such as the decrease in leaf blades and the increase in vascular bundles, results that differ from those obtained in the current study: 81.3 and 26.46 t.ha -1 .…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The fourth group was formed by C. purpureus with the Maralfalfa and Elephant varieties with the highest yields (total biomass and DMY). Under conditions of the Ecuadorian Amazon [45] (1426 mm, 23.7 °C and 83.8%, rainfall, average temperature and relative humidity) reported values higher than 90 t.ha -1 and 20 t.ha -1 of biomass and dry material; respectively. These variations are given by natural causes or by human action such as: the availability of water, development of the root system of the plant and time of year; these produce morphological changes such as the decrease in leaf blades and the increase in vascular bundles, results that differ from those obtained in the current study: 81.3 and 26.46 t.ha -1 .…”
Section: Resultsmentioning
confidence: 92%
“…In this Hence, Roca, Zamora, Zamora, and Félix [38], Herrera [43], Herrera, Garcia, and Cruz [44], and Cuervo-Vivas, Santacoloma, and Barreto [45] pointed out that the elements of the climate interact and have a marked effect on the growth and development of the species and varieties of grasses in the different months of the year; we can explain that this behavior is due to the fact that plant species exist, reproduce and endure in certain edaphoclimatic contexts; what can be considered as tolerance to those conditions. These aspects are revealed in the present study due to the differences and similarities found in terms of quality indicators, in relation to their differences in growth habit, structure and phenology of the species under study.…”
Section: Resultsmentioning
confidence: 99%